EFL Teachers Perception of Formative Assessment – A Study of Vocational School (SMK) in Indonesia - Akter, Mahmuda; Khan, Muhammad Lookman Hossain (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
The formative assessment has become a core component in teaching. The educator uses it to measure the effectiveness of learning in the classroom, and it provides information on the competencies of the students in addition to enhancing learning outcomes for the students. This study aims to investigate the vocational school teachers' perception and practices of formative assessment in the EFL classroom. This study used a qualitative research design approach. Two experienced teachers from vocational schools in central java, Indonesia participated in this study. The author collected the data from the participants using a semi-structured interview and analysed the data using descriptive qualitative method. The study result revealed that the participants have a very good understanding of formative assessment. They believed that it allows them to become more professional and the classroom assessment help students to focus more on learning materials. The teachers implement formative assessment practices regularly in their classroom.Â